(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This study aims to identify the representative wave conditions for designing the wave energy converter (WEC) in the ocean. Field wave data from a buoy station offshore a remote island of Matsu, Taiwan were adopted. They were analysed by the Representative High Wave Energy scheme and the K-means clustering scheme. Comparing results between the two schemes indicate that the K-means scheme performs better in selecting representative wave conditions for wider spectra of sea states. Furthermore, the optimal clustering numbers (K values) were investigated. The results show that 6 clusters (K values) can better reflect the overall wave energy characteristics of the sea states, and the calculated representative wave conditions can be used to evaluate the WEC design with high performances at a target marine site.